Newly identified relation of improved grasses and soil microbes towards nutrient acquisition and Greenhouse Gas (GHG) mitigation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
This study at greenhouse conditions showed an outstanding property of the plant-fungi symbiosis to reduce N2O emissions by half only with the inoculation of AMF. However, this was a longer-term measurements are needed to validate whether the effects of AMF on N2O emissions persists over time.